Mean Reversion in Profitability for Non-Listed Firms - Kjell Bjørn Nordal; Randi Næs (Norges Bank, 2009)
The presence of mean reversion in profitability at the firm level is important for valuation and prediction of growth and earnings. We investigate the mean reversion in accounting profitability for Norwegian non-listed firms for the period 1988-2006. We find a mean reversion rate of about 0.44. This is higher than found in other studies. We also find that small firms have a higher mean reversion rate than large firms. Previously, price-to-book ratios have been used to investigate changes in profitability over time for listed firms. We examine bankruptcy risk as an alternative variable for unlisted firms. We find that bankruptcy risk may help explain changes in profitability, but the results are not as strong as found in previous work.
hdl:11250/2497611
Keywords: G10; G30; 330; non-listed firms; profitability; mean reversion